Avaliação de um construto para medir o grau de maturidade das empresas quanto as tecnologias de gestão: uma aplicação do modelo de escala gradual no caso SIMAP - Nogueira, Maria Emanuela Ferreira (2012)
The current competitive and demanding market make the companies look increasingly, a high degree of quality, thus ensuring their survival. To seek this constant updating of technologies, the companies need to update their organizational management models among other systems. Each day brings new models and methods of implementation of management systems, where quality is no longer a distinctive element, but absolutely essential. In this approach, logistics has become an essential tool for reducing costs and improving quality. For the good performance of the logistics activities of an organization it is necessary to evaluate its performance in the market and the possibilities of an assessment of logistics performance is benchmarking. The present study aims to apply the Item Response Theory, in particular, the Rating Scale Model, to analyze the degree of maturity in relation to management technologies, based on the construct of the Monitoring System Productive Arrangements (SIMAP), which aims to present the competitive benchmarking. The data used in this work are of secondary nature, from 39 items valued at 109 companies registered in SIMAP. The results revealed in the study had indicated that the technology “Method of investment analysis”, “Capability studies”, “Participatory programs”, “Costing ABC”, “Philosophies and Tools JIT”, “Time setup”, “ISO 14001” and “SA8000” provide a major contribution to measure the degree of maturity of the companies regarding to the management tools. The company with the highest degree of maturity, 71.99 (in the range of (μ = 50, σ = 10)), is a midsize company, which belongs to the productive chain of food and beverage manufacturers in the link of the dairy / barley / water and soft drinks, which operates in regional market, with production geared to supply the Northeast. The smaller degree of maturity, 31.63, was found in a small business, belonging to the productive chain of construction, linked to the red ceramic as a retailer, also serving the regional market.